Global Economic Effect of Covid-19 on Unemployment and Quality of life of Young Adults - Otegbayo Bolajoko Elizabeth; Olugu Ezutah Udoncy; Siti Norida Wahab; Ahmad Bin Ibrahimand Otegbayo Christy Olubunmi (Communications of International Proceedings, 2020)
The global economic crisis as a result of Covid-19 might increase the risk of employment insecurity and poor quality of life among young adults. This study evaluates the influence of the Covid-19 pandemic on employment insecurity and quality of life among young adults. Covid-19 pandemic is negatively affecting the global economy given that majority of business establishments and companies are compelled to temporarily shut down. As a result, some establishments or organizations are unable to meet up with the financial responsibilities of their companies. Therefore, workers are being laid off temporarily or permanently, businesses and companies are downsizing, cost of goods and services is spiking. Consequently, there is a further increase in employment insecurity among young adults. Hence, there is a likelihood of a reduction in the standard of living for the young adult population. A collective effort by the government and major stakeholders is required to ensure rigorous enforcement of Covid-19 precautionary measures. Additionally, adequate social or welfare support should be put in place for individuals who have lost their jobs and low-income earners. This will help minimize the severity of the economic crisis and employment insecurity among young adults globally. The study culminates with directions for further studies.
Keywords: Covid-19; Global Economy; Employment Insecurity; Young Adults; Informal worker; Quality of Life.